Numerical and Experimental Study on Deicing of Wind Turbine Blades by Electric Heating Under Complex Flow Field - Jianwei Li; Panpan Yang; Xuemei Huang; Leian Zhang; Jinghua Wang (Machines)
Wind turbine blades are prone to icing in cold environments, which leads to decreased aerodynamic performance, increased power loss, and even endangers the safe and stable operation of wind turbines. Electric heating anti-deicing method is the most effective solution because of its flexible control, rapid response, and high deicing efficiency. However, in the process of blade high-speed rotation, the complex flow field effect significantly affects the blade heat transfer performance, which leads to the problems of high energy consumption, low heat utilization, and uneven heating of traditional electric heating anti-icing/deicing methods, limiting their application effect in complex working conditions. Based on the physical mechanism and heat exchange characteristics of electric heating deicing of wind turbine blades, a coupled flow–heat transfer numerical model suitable for complex flow field conditions was constructed in this study, aiming to realize the dynamic simulation of the global temperature field and the phase transition process of ice sheets under different heating modes. Furthermore, the deicing efficiency characteristics of continuous heating and cyclic heating modes were compared and analyzed. The blade tip section of a Sinoma87.5 was taken as the experimental object, and the deicing experiment of blade by electric heating was carried out under artificial ice-covering laboratory conditions. The simulation and experimental results show that the deicing process by electric heating can be divided into three typical stages: initial temperature rise, stagnation, and rapid temperature rise. Under the influence of incoming flow conditions, the temperature rise of the front stagnation point region lags behind that of the windward side, and the steady-state peak temperature is lower. Compared with the cyclic heating mode, the continuous heating mode can enter and cross the stagnation period more quickly. The peak steady-state temperature of the continuous heating mode is 24.2 °C, and the deviation from the simulation result is only 2.8 °C, which is within the acceptable error range, effectively verifying the reliability of the numerical calculation model established.